Oil palm seedling growth in media amended with fifty percent dairy farm effluent compost under reduced fertiliser input - MOHD. RASHID MOHD. RAKIB; NUR AAINAA HASBULLAH; CLAMENT FUI SEUNG CHIN; BORHAN ABDUL HAYA; N. J. MAYZAITUL-AZWA; SITI SULIZA SALAMAT; NOR JAWAHIR ABU; KHIM PHIN CHONG; S. SYAMSIA (Asian Journal of Agriculture, 2026)
Abstract. Rakib MRM, Hasbullah NA, Chin CFS, Haya BA, Mayzaitul-Azwa NJ, Salamat SS, Abu NJ, Chong KP, Syamsia S. 2026. Oil palm seedling growth in media amended with fifty percent dairy farm effluent compost under reduced fertiliser input. Asian J Agric 10 (1): g100174. https://doi.org/10.13057/asianjagric/g100174. Conventional oil palm nursery practices rely heavily on mineral fertilisers, which promote short-term growth but cause adverse environmental impacts. Organic amendments in planting media have the potential to sustain seedling development while reducing dependence on mineral fertilisers. This study evaluated the growth and biomass accumulation of oil palm seedlings at the main nursery stage by amending Dairy Farm Effluent Compost (DFEC) to planting media under reduced mineral fertiliser input. Three-month-old seedlings were transplanted into either 100% mineral soil or a 1:1 mixture of mineral soil and DFEC, with varying mineral fertiliser rates. Treatments were arranged in a Completely Randomized Design (CRD). Ten replications (n = 10) were used for non-destructive measurements, while five randomly selected seedlings per treatment (n = 5) were used for destructive biomass and root assessments at nine months after transplanting. Data were analysed using Analysis of Variance (ANOVA) followed by Tukey’s test. Seedlings grown in DFEC-amended media exhibited significantly greater height and bole circumference compared to those in 100% mineral soil with full-rate fertiliser application. Frond production (14-16 fronds) and root numbers (15-24 primary roots) did not differ significantly among treatments. However, dry matter accumulation in fronds and stems was markedly higher in DFEC-amended seedlings, irrespective of fertiliser application, suggesting that DFEC amendment alone was able to sustain seedling growth under the conditions tested. Notably, addition of 50% DFEC to the mineral soil, either with half-rate mineral fertiliser or without fertiliser performed as well as or better than the 100% mineral soil with full-rate fertiliser, in terms of plant height, bole circumference, and fronds, stem and total dry biomass. The findings indicate that dairy farm effluent compost can potentially serve as a sustainable amendment in oil palm nursery systems, providing agronomic benefits while supporting nutrient recycling and reducing the environmental footprint of early-stage cultivation.